Is neocolonialism existing in global surgery practice? An analysis of a web-based survey amongst global surgery practitioners - Justina O. Seyi-Olajide; Mary Brindle; Omolara Faboya; Ambereen Sleemi; Omolara Williams; Emmanuel A. Ameh (Inishmore Laser Scientific Publishing Ltd, 2024)
# Background There is an ongoing discussion for decolonization of global health and a resetting of global health partnerships and practices. However, a lack of understanding and agreement on the issues involved remain a major limitation. The aim of this study was to understand and identify the manifestations of neocolonialism in global surgery practice. # Methods This was a qualitative web-based survey of 445 low-and middle-income countries (LMICs) and high-income countries (HICs) global surgery practitioners. We also captured through focussed interviews their perceptions and reported manifestations of neocolonialism in global surgery. # Results The majority (73.9%) came from LMICs, while 26.1% were from HICs. Surgeons formed the largest group (57.6%), with many having extensive experience (38.7% with over 10 years in global surgery). Neocolonialism was defined as an unequal power dynamic favoring HIC agendas. Uncompensated work by LMICs staff and funding disparities were identified as neocolonial practices by HICs participants. Limited research capacity and frustrated LMICs providers were seen as consequences. Factors enabling neocolonialism included limited local funding and training priorities set by funders, not local needs. More than 75% of participants agreed that fear of losing HIC support was a major barrier to open communication about neocolonialism in global surgery. # Conclusions This study among global surgery players unbderscores existence and experiences of neocolonialism in global surgery. The impact of this practice and the enablers need to be urgently addressed by implementing mitigating solutions.